Public road driving tests of Toyota Prius equipped with high-efficiency III-V triple-junction PV modules - Masuda Taizo; Yamaguchi Masafumi; Iwasaki Shinya; Nakado Takashi; Takamoto Tatsuya; Nishioka Kensuke (EPJ Photovoltaics)
This paper presents the measurement results of public road tests of a solar-powered plug-in hybrid electric vehicle that is equipped with PV modules (2–9) that have a rated-output power of 860 W. The vehicle-integrated PV modules consist of III-V-based triple-junction solar cells with an average conversion efficiency of approximately 34%. The measurement results indicate that the number of plug-in charging cycles can be reduced significantly by integrated PV modules, which increase the convenience of use of the battery-based vehicles. Even energy self-sufficiency was achieved for the neighborhood driving pattern. Further, in Aichi prefecture, Japan, the annual solar-powered driving range reached 6211 km in the year 2021. As the average annual driving range of passenger cars in Japan is approximately 10,000 km, it was experimentally confirmed that CO2 emission from passenger cars in Japan can be reduced by approximately 62% by installing vehicle-integrated PV modules. Future direction for PV modules and solar powered vehicles is also discussed.